1998
DOI: 10.1111/j.1151-2916.1998.tb02681.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Peptization and Ethanol Washing on the Pore‐Structure Evolution of Sol‐Gel‐Derived Alumina Catalyst Supports

Abstract: Alkoxide-derived boehmite precipitates were subjected to different post-precipitation treatments to obtain a peptized sol, an unpeptized slurry, and an ethanol-washed gel precipitate. These materials were dried further to obtain the corresponding gels. Changes in the surface area, porosity, and pore size with temperature and the phase-transformation behavior from ␥-alumina to ␣-alumina were studied using X-ray diffractometry, differential scanning calorimetry, and physical adsorption/desorption measurements. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…M acroporous ceramics provide the possibility to combine high permeability with good mechanical, thermal, and chemical stability which is attractive for a wide range of industrial applications 1–3 . Liquid metal filters of alumina, 4 diesel soot filters of alumina and zirconia 5 , and catalyst supports of alumina and corderite 6–8 are examples where porous ceramics are already commercially established, while other applications including e.g. hard tissue and bone scaffolds are still in development 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…M acroporous ceramics provide the possibility to combine high permeability with good mechanical, thermal, and chemical stability which is attractive for a wide range of industrial applications 1–3 . Liquid metal filters of alumina, 4 diesel soot filters of alumina and zirconia 5 , and catalyst supports of alumina and corderite 6–8 are examples where porous ceramics are already commercially established, while other applications including e.g. hard tissue and bone scaffolds are still in development 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Peptization of the amorphous TiO 2 also greatly affects the packing behavior of TiO 2 powder. Kumar and co-workers 4,5 and Nair et al 9 compared the packing behavior of unpeptized and peptized samples and concluded that the lessagglomerated samples that were obtained from the peptized species created an efficient packing of particles, whereas the unpeptized species favored the formation of structures with greater porosity and larger pore sizes.…”
Section: Introductionmentioning
confidence: 99%
“…A further process is required to form the MnO2 structures. It was proved that, if the material is processed in an alcohol-based environment, a fine growth unit for formation of metal oxide is likely to form [33,34]. To avoid a process at high temperatures that can result in a For material characterization, X-ray diffraction (XRD) (Bruker D-8 diffractometer, Madison, WI, USA) was used for the determination of crystal structure of synthesized products.…”
Section: Resultsmentioning
confidence: 99%
“…A further process is required to form the MnO 2 structures. It was proved that, if the material is processed in an alcohol-based environment, a fine growth unit for formation of metal oxide is likely to form [33,34].…”
Section: Resultsmentioning
confidence: 99%